The Effect of Family Psychoeducation Therapy on Family Self-Esteem in Patients with Schizophrenia - Rayi Ilhamifan; Rizka Yunita; Achmad Kusyairi (KHD Production, 2025)
Schizophrenia is one of the most serious and most common mental disorders in Indonesia. More than half of the burden of families caring for people with schizophrenia is in the moderate category. Families feel anxious and sad about the condition of people with schizophrenia; negative assessments from society about schizophrenia also further burden the family's condition in adapting to the presence of schizophrenia patients in the family. The purpose of this study was to analyze the Effect of Family Psychoeducation Therapy on Family Self-Esteem in Patients with Schizophrenia. This type of research is pre-experimental with a one-group pretest-posttest approach. Data collection was carried out from August 1 to August 31, 2024. The study population was 37 families who had family members with schizophrenia, and the sample was 37 families who had family members with schizophrenia, using the total sampling technique. Family Psychoeducation Therapy consists of 6 sessions, each carried out per week, and the duration of psychoeducation therapy is 45 minutes. The measuring instrument used for family self-esteem is the self-esteem scale. The study results showed that 15 respondents had 40.5% moderate self-esteem before psychoeducational therapy, while 20 respondents had 54.1% high self-esteem after being given psychoeducational therapy. After the Wilcoxon test was carried out, it showed a p-value of 0.000, indicating the influence of family psychoeducational therapy on family self-esteem in patients with schizophrenia. This study shows that family psychoeducational therapy is vital in the process of families caring for their family members with schizophrenia. This also shows the importance of the role of the family in the healing process of sick family members.